Nutritional Parenting as an Effort to Prevent Stunting in Toddlers on Mantang Island - Dewi Mey Lestanti Mukodri; Rita Ridayani; Neny San Agustina (Alliance oh Health Activists (AloHA), 2021)
The quality and quantity of nutrition in children's food needs attention because it is a support for body growth. Good nutritional intake for children needs to be supported by the mother's ability to provide good care, in terms of providing food, maintaining personal and environmental hygiene, as well as seeking treatment. This study aims to analyze the differences in nutritional parenting patterns for toddlers before and after being given nutritional counseling using BOCESTING (booklets for stunting prevention) in Mantan Island, Bintan Regency, Riau Islands. The design of this experimental research is one group pretest and posttest. The sample is 43 mothers of children under five. Differences in the level of knowledge and nutrition parenting between before and after the intervention were analyzed using paired sample t-test. The results of the analysis showed the value of p = 0.000, so it can be interpreted that there is a difference in the level of knowledge between before and after giving counseling using BOCESTING. Thus, it can be concluded that counseling using BOCESTING is effective for increasing knowledge in the context of preventing stunting by mothers of children under five. Keywords: stunting; BOCESTING booklet; knowledge